Vitamin K2 Can Rescue the Dexamethasone-Induced Downregulation of Osteoblast Autophagy and Mitophagy Thereby Restoring Osteoblast Function In Vitro and In Vivo - Chen, Liang; Shi, Xiang; Weng, She-Ji; Xie, Jun; Tang, Jia-Hao; Yan, De-Yi; Wang, Bing-Zhang; Xie, Zhong-Jie; Wu, Zong-Yi; Yang, Lei (Frontiers in Pharmacology, 2020)
Chronic long-term glucocorticoids (GC) use is associated with glucocorticoid-induced osteoporosis (GIOP) by inhibiting the survival and impairing the functions of osteoblasts. Autophagy and mitophagy play key roles in osteoblast differentiation, mineralization and survival, and mounting evidence have implicated osteoblast autophagy and mitophagy as a novel mechanism in the pathogenesis of GIOP. Vitamin K2 (VK2) is an essential nutrient supplement that have been shown to exert protective effects against osteoporotic bone loss including GIOP. In this study, we showed that the glucocorticoid dexamethasone (Dex) deregulated osteoblast autophagy and mitophagy by downregulating the expression of autophagic and mitophagic markers LC3-II, PINK1, Parkin. This consequently led to inhibition of osteoblast differentiation and mineralization function in vitro. Interestingly, co-treatment with VK2 significantly attenuated the Dex-induced downregulation of LC3-II, PINK1, Parkin, thereby restoring autophagic and mitophagic processes and normal osteoblastic activity. In addition, using an established rat model of GIOP, we showed that VK2 administration can protect rats against the deleterious effects of Dex on bone by reinstating autophagic and mitophagic activities in bone tissues. Collectively, our results provide new insights into the role of osteoblast autophagy and mitophagy in GIOP. Additionally the use of VK2 supplementation to augment osteoblast autophagy/mitophagy may significantly improve clinical outcomes of GIOP patients.